SEEMIOTIKA KOMUNIKASI PADA MOTTO “KOTA MATARAM MAJU, RELIGIUS DAN BERBUDAYA” - Diah Maya Apsari (JURNAL ILMIAH GLOBAL EDUCATION, 2022)
Mataram City has a motto that is Mataram City Forward, Religious and Cultured. (Explanation of the meaning of the motto/vision and mission one by one, indicators of the motto one by one). This motto becomes the spirit, soul, and spirit of the Mataram City Government and the people of Mataram City in carrying out activities and life in Mataram City. The results of this study Semiotics of communication contained in the motto of the city of Mataram is advanced, religious and cultured is not just a slogan but has the meaning of hopes and ideals that are always endeavored by the Mataram city government as the highest policy holder in the city of Mataram. To build the city of Mataram which is advanced in all aspects. This study uses a qualitative methodology. Bogdan and Taylor in Moleong (2007: 4) define qualitative research methodology as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. Meanwhile, Kirk and Miller in Moleong (2007) define qualitative research as a particular tradition in social science that is fundamentally dependent on human observations both in its area and in its terminology. This study aims to find out what the semiotics of communication are contained in the Motto "Maju Mataram City is Advanced, Religious and Cultured". The difference between the previous research and what the researcher is going to do is that the previous research examined "semiotic analysis of communication in other sentences, while this study examines the meaning of semiotics in the motto of Mataram city, namely "Maju Kota Maju, Religious, and Cultured".